2019
DOI: 10.1111/cei.13270
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni PCR+-infected individuals in the Sudan present elevated systemic levels of chemokines when compared to uninfected and egg+ cohorts

Abstract: Infections withSchistosoma mansoni remain a major health problem in the Sudan where endemic communities, such as those in Kassala and Khartoum states, continue to face severe social-economic difficulties. Our previous immunoepidemiological findings revealed different immune [cytokine and S. mansoni egg (SEA) antibody] profiles in individuals with active infections (eggs in stool n = 110), individuals positive for S. mansoni via polymerase chain reaction (PCR) using sera (Sm PCR + n = 63) and those uninfected (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 35 publications
3
6
0
Order By: Relevance
“…In a recent study from Cha et al, it was revealed that schistosomiasis continues to burden populations in non-stable communities of the Sudan [1]. In correlation with our previous studies from the Sudan [2,3], Cha and colleagues also found strong associations between infection and available latrines-since infections are obtained in fresh water sources from snails releasing cercariae, the infectious stage. Thus, despite large-scale programmes designed to tackle schistosomiasis [4], this chronic helminth infection remains a severely neglected tropical disease in the Sudan [5].…”
Section: Introductionsupporting
confidence: 63%
See 4 more Smart Citations
“…In a recent study from Cha et al, it was revealed that schistosomiasis continues to burden populations in non-stable communities of the Sudan [1]. In correlation with our previous studies from the Sudan [2,3], Cha and colleagues also found strong associations between infection and available latrines-since infections are obtained in fresh water sources from snails releasing cercariae, the infectious stage. Thus, despite large-scale programmes designed to tackle schistosomiasis [4], this chronic helminth infection remains a severely neglected tropical disease in the Sudan [5].…”
Section: Introductionsupporting
confidence: 63%
“…This group could be individuals with dying, menopausal or single worm infections, or an early infection. In terms of schistosome-specific antibody levels, this group showed increased levels of worm-specific IgG2 [3] but lower egg-specific IgG4 levels when compared to egg-positive individuals [2].…”
Section: Introductionmentioning
confidence: 77%
See 3 more Smart Citations